2013
DOI: 10.1093/hmg/ddt315
|View full text |Cite
|
Sign up to set email alerts
|

The UPF3B gene, implicated in intellectual disability, autism, ADHD and childhood onset schizophrenia regulates neural progenitor cell behaviour and neuronal outgrowth

Abstract: Loss-of-function mutations in UPF3B result in variable clinical presentations including intellectual disability (ID, syndromic and non-syndromic), autism, childhood onset schizophrenia and attention deficit hyperactivity disorder. UPF3B is a core member of the nonsense-mediated mRNA decay (NMD) pathway that functions to rapidly degrade transcripts with premature termination codons (PTCs). Traditionally identified in thousands of human diseases, PTCs were recently also found to be part of 'normal' genetic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 71 publications
6
104
0
1
Order By: Relevance
“…In humans, two UPF3 paralogs, UPF3 and UPF3X (also called UPF3A and UPF3B, respectively), differently modulate NMD activity (Chan et al, 2009;Kunz et al, 2006;Lykke-Andersen et al, 2000;Serin et al, 2001) in ways that, like UPF1 and another NMD factor, UPF2, have been shown to be crucial for, for example, normal neuronal maturation and development (Colak et al, 2013;Jolly et al, 2013;Laumonnier et al, 2010;Lou et al, 2014;Nguyen et al, 2012Nguyen et al, , 2013Tarpey et al, 2007). UPF3 or UPF3X are generally associated with exon junction complexes (EJCs; see below) that are deposited in the nucleus upstream of newly spliced exon-exon junctions, whereas UPF2 is generally associated with EJCs after newly synthesized mRNAs are exported to the cytoplasm (Kim et al, 2001;Lejeune et al, 2002;Lykke-Andersen et al, 2001).…”
Section: Central Nmd Factors In Human Cellsmentioning
confidence: 99%
“…In humans, two UPF3 paralogs, UPF3 and UPF3X (also called UPF3A and UPF3B, respectively), differently modulate NMD activity (Chan et al, 2009;Kunz et al, 2006;Lykke-Andersen et al, 2000;Serin et al, 2001) in ways that, like UPF1 and another NMD factor, UPF2, have been shown to be crucial for, for example, normal neuronal maturation and development (Colak et al, 2013;Jolly et al, 2013;Laumonnier et al, 2010;Lou et al, 2014;Nguyen et al, 2012Nguyen et al, , 2013Tarpey et al, 2007). UPF3 or UPF3X are generally associated with exon junction complexes (EJCs; see below) that are deposited in the nucleus upstream of newly spliced exon-exon junctions, whereas UPF2 is generally associated with EJCs after newly synthesized mRNAs are exported to the cytoplasm (Kim et al, 2001;Lejeune et al, 2002;Lykke-Andersen et al, 2001).…”
Section: Central Nmd Factors In Human Cellsmentioning
confidence: 99%
“…[25][26][27] Indeed, premature neurogenesis has been associated to gross brain abnormalities in a thalassemia/mental retardation syndrome X-linked (ATRX), consistently with the microcephaly observed in patients affected by this disorder. 28,29 Similarly, accelerated cell cycle and overproduction of GABAergic inhibitory neurons were described in iPSC-derived brain organoids of Autism Spectrum Disorder (ASD) patients characterized by macrocephalia.…”
mentioning
confidence: 88%
“…42,49,50 While the underlying basis for its role in neural development and cognition are not known, in vitro studies have shown that UPF3B promotes neural differentiation and it is regulated by neurally expressed microRNAs that influence neural self-renewal vs. differentiation decisions. 20,29 UPF3B also shapes the unfolded protein response, a pathway critical for normal neural development. 21 Until recently, the functional role of UPF3B's paralog partner-UPF3A-has been unclear.…”
Section: The Upf3 Gene Paralogsmentioning
confidence: 99%
“…8,35,50 UPF3B promotes the differentiation of neural progenitor cells and may be involved in the ability of NMD to influence neural proliferation versus differentiation decisions by virtue of its ability to degrade specific transcripts. 20,29 Thus, by subtly controlling the stabilities of batteries of mRNAs, the UPF3B branch of NMD may have played an important role in the evolution of the vertebrate brain.…”
Section: Neofunctionalization: Acquisition Of Nmd Suppressionmentioning
confidence: 99%